Efectos del desecamiento del suelo sobre el metabolismo de nitrógeno en tres cultivares de maíz (Zea mays L.). - Pereyra Rossiello, R; Silvestre Fernandes, M; Mazur, N. (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2022)
The effects of water stress on the nitrogen metabolism of three corn (lea mays L ) cultivars (Piranao, Centrahnex, IPEACS III) were studied. Measurements were made of the Relative Water Content (RWC); nitrate-reductase activity (NRA) as well as accumulation of amino-N, ammonia-N, free proline and protein-N in the plant tissues. Cultivar Piranio kept a higher RWC and NRA through the desiccation period, and accumulated the lowest levels of ammonia-N and amino-N in its foliar tissues. The performance of cultivar Centrahnex was poor but cultivar IPEACS III was the most severely affected by the imposed water stress regime in terms of the metabolic parameters studied. All three cultivars exponentially acumulated proline with the length of the stress period. It is suggested that further studies should be done on proteolytic activities and de novo synthesis of proline for a better understanding of the effects of metabolites accumulation on water stress resistance in corn plants.